The effect of antioxidant dietary supplements and diet-derived circulating antioxidants on vitiligo outcome: evidence from genetic association and comprehensive Mendelian randomization - Ni, Yao; Zhang, Youqian; Sun, Jingying; Zhao, Lingyi; Wu, Bo; Ye, Jianzhou (Frontiers in Nutrition, 2024)
Background: Previous studies have indicated that antioxidant diets may have a positive impact on vitiligo by interfering with oxidative stress mechanisms. However, there has been a lack of research utilizing the Mendelian randomization (MR) method to analyze the relationship between antioxidant diet intake and vitiligo. Methods: In this study, we employed both univariate Mendelian randomization (UVMR) and multivariate Mendelian randomization (MVMR) approaches. The specific antioxidant dietary supplements (such as coffee intake, green tea intake, herbal tea intake, standard tea intake, and average weekly red wine intake) as well as diet-derived circulating antioxidants, including Vit. C (ascorbate), Vit. E (α-tocopherol), Vit. E (γ-tocopherol), Carotene, Vit. A (retinol), Zinc, and Selenium(N=2603-428860) were significantly associated with independent single nucleotide polymorphisms (SNPs). We obtained pooled statistics on vitiligo from a meta-analysis of three genome-wide association studies (GWASs) of European ancestry, including 4,680 cases and 39,586 controls. Inverse variance weighted (IVW) was employed as the primary analytical method, and sensitivity analysis was conducted to assess the robustness of the main findings. Results: Genetically, coffee intake [odds ratio (OR)=0.17, 95% confidence interval (CI) 0.07-0.37, p =1.57×10 −5 ], average weekly red wine intake (OR=0.28, 95% CI 0.08-1.00, p =0.049), and standard tea intake (OR=0.99, 95% CI 0.98-0.99, p =5.66×10 -7 ) were identified as protective factors against vitiligo. However, no causal effect between the intake of other antioxidant diets and vitiligo was found. Moreover, no instances of pleiotropy or heterogeneity were observed in this study.Our study indicates that coffee, standard tea, and red wine consumption can potentially reduce the risk of vitiligo. However, there is insufficient evidence to support that other antioxidant diets have a significant effect on vitiligo.